Innovation in Indonesian Language Learning Models in Elementary Schools: A Systematic Literature Review Using the PRISMA Method - Nada Nadhiroh Ramadhani; Putri Hana Pebriana; Rifdah Afifah; Yollita Sabani; Riko Fahrezi; Mutia Saqillah Ahyar; Ahmad Rafid Alfarizi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Innovation in Indonesian language learning models is key to addressing literacy challenges in the digital era. This study aims to identify, map, and synthesize the trends of innovative Indonesian language learning models in elementary schools within the last five years (2021–2026). Method: This study employed a Systematic Literature Review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Data were collected from reputable databases including Google Scholar, SINTA, DOAJ, and ERIC using specific Boolean operators. After a rigorous screening process, 15 key articles meeting the inclusion criteria were selected for comprehensive analysis. Results: The findings reveal four dominant innovation trends: (1) the integration of digital technology and Artificial Intelligence (AI) in creative writing; (2) the implementation of Project-Based Learning (PjBL) rooted in local wisdom; (3) the adoption of differentiated learning to address the heterogeneity of literacy skills; and (4) the utilization of multimodal media to enhance reading and listening comprehension. These innovations have been shown to significantly improve student engagement, learning motivation, and Higher-Order Thinking Skills (HOTS). Conclusion: The transformation from conventional, teacher-centered models to technology-integrated and student-centered approaches is crucial for enhancing national literacy quality. This study recommends prioritizing teacher professional development in digital competence to ensure the sustainability of these innovative models in elementary classrooms.